Heterogeneous Suzuki cross-coupling reactions over palladium/hydrotalcite catalysts - Mora, Manuel; Jiménez-Sanchidrián, César; Ruiz, J. Rafael (Journal of colloid and interface science, 2006)
The efficiency of various heterogeneous solids consisting of palladium supported on hydrotalcite as catalysts in the Suzuki cross-coupling reaction between bromobenzene and phenylboronic acid was studied. Based on the catalytic activity results, the reaction develops to an acceptable extent with 100% selectivity at moderate temperatures in the presence of some of the catalysts. The best results were provided by a catalyst consisting of an acetate–pyridine complex of Pd supported on hydrotalcite that gave high conversion values even after three reuses. The reactions conditions were very mild (a temperature of 55 °C and atmospheric pressure). In fact, the catalyst provided conversion and selectivity results surpassing those of existing heterogeneous phase catalysts and most homogeneous phase catalysts for the same purpose.